APPLYING BETA‐TYPE SIZE DISTRIBUTIONS TO HEALTHCARE COST REGRESSIONS. (8th July 2013) - Jones, Andrew M.; Lomas, James; Rice, Nigel
SUMMARY This paper extends the literature on modelling healthcare cost data by applying the generalised beta of the second kind (GB2) distribution to English hospital inpatient cost data. A quasi‐experimental design, estimating models on a sub‐population of the data and evaluating performance on another sub‐population, is used to compare this distribution with its nested and limiting cases. While for these data the beta of the second kind (B2) distribution and generalised gamma (GG) distribution outperform the GB2, our results illustrate that the GB2 can be used as a device for choosing among competing parametric distributions for healthcare cost data. Copyright © 2013 John Wiley & Sons, Ltd.